Amniotic fluid CD11b levels in pregnancies complicated by preterm prelabor rupture of membranes - Soucek, Ondrej; Kacerovsky, Marian; Musilova, Ivana; Pliskova, Lenka; Bolehovska, Radka; Andrys, Ctirad (Journal of maternal-fetal & neonatal medicine, 2022)
OBJECTIVE: CD11b is an integrin molecule located on the surface of leukocytes. CD11b is involved in the processes of cell adhesion and migration. Expression of CD11b increases during inflammation. Therefore, this study was aimed at the evaluation of concentrations of CD11b in the amniotic fluid from pregnancies complicated by preterm prelabor rupture of the membranes (PPROM), with respect to the presence of microbial invasion of the amniotic cavity (MIAC), intra-amniotic inflammation (IAI), and microbial-associated IAI (the presence of both MIAC and IAI). METHODS: Eighty women with singleton pregnancies complicated by PPROM were included. Amniotic fluid samples were obtained by transabdominal amniocentesis. Amniotic fluid CD11b concentrations were determined by enzyme-linked immunosorbent assay. MIAC was determined by a non-cultivation approach. IAI was defined by a bedside amniotic fluid interleukin-6 concentration ≥745 pg/mL. RESULT: Women with MIAC or microbial-associated IAI had higher CD11b concentrations in the amniotic fluid than women without these complications (with MIAC: median 0.31 ng/mL versus without MIAC: median 0.17 ng/mL, p = .001; with microbial associated-IAI: median 0.35 ng/mL versus without microbial-associated IAI: median 0.16 ng/mL; p =.02). The presence of IAI was not associated with elevated CD11b concentrations. A weak negative correlation was found between amniotic fluid CD11b concentrations and interleukin-6 concentrations (rho = 0.26; p = .02). CONCLUSIONS: MIAC and microbial-associated IAI are characterized by higher amniotic fluid CD11b concentrations in pregnancies complicated by PPROM.
Keywords: plodová voda; gestační stáří; Infant, Newborn; Pregnancy; těhotenství; Gestational Age; novorozenec; předčasný odtok plodové vody; Amniotic Fluid; Chorioamnionitis; Fetal Membranes, Premature Rupture; amniocentéza; Humans; lidé; ženské pohlaví; chorioamnionitida; Amniocentesis; Female